Oxidative and abrasive wear of multiphase AlSi0.75TiMnFeCux (X = 0, 0.25, 0.5) high entropy alloy under non-lubricating reciprocating motion - Lee, Hansung; Kim, Minsu; Sharma, Ashutosh; Ahn, Byungmin (Powder Metallurgy, 2023)
In this study, dry sliding wear of AlSi0.75TiMnFeCux (x = 0, 0.25, 0.5) high-entropy alloy (HEA) produced through mechanical alloying (MA) and spark plasma sintering (SPS) was studied. The microstructure and phase evolution were examined using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The wear behaviour of HEAs was assessed by reciprocating wear monitor under a dry air atmosphere. The findings demonstrated that AlSi0.75TiMnFeCux HEAs were multiphase body-centred cubic (BCC/B2) solid solution structured with complex µ-, L21, and Laves. It was discovered that the microhardness and wear behaviour of AlSi0.75TiMnFeCux were comparable to AlSi0.75TiMnFe HEA after the addition of Cu up to 0.25 molar ratio. The maximum hardness of the AlCu0-0.5FeMnTiSi0.75 HEAs reached around 1021–1035 HV. The tribology results show that an oxidative wear in AlSi0.75TiMnFe while the mixed adhesive-abrasive wear mechanism was prominent in the AlSi0.75TiMnFeCu0.25-0.5 HEAs.
Keywords: Automotives; Dry sliding wear; High entropy alloys; Microstructure evolutions; Multiphases; Phase evolutions; Reciprocating motion; Spark-plasma-sintering; Wear behaviors; X ray scanning; automotive; friction; high entropy alloy; powder metallurgy; wear